Exploring the relationship between corporate social responsibility and firm competitiveness. Issue 1 (1st January 2020) - Lu, Jintao; Ren, Licheng; Yao, Siqin; Qiao, Jiayuan; Mikalauskiene, Asta; Streimikis, Justas
Abstract: This study deals with the relationship between corporate social responsibility (CSR) and firm competitiveness. Based on the comprehensive literature review, the theoretical model, providing linkages between CSR and corporate competences, has been developed. The created model was empirically tested, and the case study in Lithuania was conducted based on the assessment of influence of different social responsibility dimensions (environmental, social, economic, shareholder and voluntariness) on separate elements of competitiveness (financial capacity, quality of production, satisfied needs of consumers, efficiency, introduction of innovations and company's image). The survey of 33 Lithuanian companies, i.e., all companies in Lithuania that have joined Global Compact, was performed by employing questionnaires. The conducted empirical research confirms that separate social responsibility dimensions (environmental, social, economic, shareholder, voluntariness) differently affect separate elements of competitiveness: financial capacity, quality of production, satisfied needs of consumers, efficiency, introduction of innovations and company's image. It has been found that neither the quality of production nor the possibilities for introduction of innovations in a company are affected by the dimensions of social responsibility. Whereas company's image, reputation and the factor of satisfied needs of consumers are affected by all dimensions of social responsibility that have been analysed. It has been noticed as well that the element of competitiveness, i.e., financial capacity, is affected by environmental and economic social responsibility dimensions; whereas, productivity and work efficiency are mostly related to social, shareholder and philanthropic dimensions. The main input of this paper is the definition of linkages between specific Corporate Social Responsibility dimensions addressed by the Global Compact and the main elements of competitiveness that have been identified based on rigorous and systematic literature review. The paper applies a completely different approach compared to the other studies that are investigating the impact of CSR on competitiveness via moderation and mediation analysis. The main approach followed in this paper is the qualitative assessment that has several limitations and advantages.